ALLELIC VARIABILITY OF CROATIAN WHEAT CULTIVARS AT THE MICROSATELLITE LOCUS XGWM261 - Krešimir Dvojković; Zlatko Šatović; Georg Drezner; Daryl J. Somers; Alojzije Lalić; Dario Novoselić; Daniela Horvat; Sonja Marić; Hrvoje Šarčević (Poljoprivreda, 2010)
The plant height of wheat is an important quantitative trait, controlled by several genes with strong effect. However, in worldwide wheat breeding, only several of those genes have been used. Rht8 (Reduced Height Gene) is especially important in agro-climatic conditions of South-East Europe. Because of its close linkage with dwarfing gene Rht8, microsatellite marker gwm261 has been accepted as the diagnostic molecular marker for gene Rht8. In this study, allelic variability at the locus Xgwm261 for 122 Croatian and foreign wheat cultivars by means of microsatellite marker gwm261 was determined. A 192 base pairs allele at the locus Xgwm261 was found for 84 Croatian cultivars. The genetic heritage of Croatian cultivars at the locus Xgwm261 is the consequence of new parental components usage, carriers of short plant and early maturity attributes and the consequent selection of progeny with these traits during breeding process. The results of this research will be helpful in characterization of domestic wheat cultivars, as well as in more accurate selection of parents for hybridization purposes.